Ill assume you mean for an are of a rectangle. w will stand for width. So you know the equation for a rectangle is L*W, so if length is 7W, then the area is 7W*W=Area or 7W^2
As a term of an expression in math, 72w means 7 times w
7w - 4w - 6w = (7 - 4 - 6)w = -3w
"16-7w plus 14-6w" is an algebraic expression - not an equation nor an inequality. It cannot be solved. So there is no way to determine the value of w and therefore the value of w-1.
Written out f(w) = w^2 + 7w + 12 there is no particular answer since it depends on what w is equal to. normally this type of question is posited as "Solve for w with f(w) = 0?" or to change its form to (ax + b)(cx + d) if f(w) = w^2 + 7w + 12 and f(w) = 0 then 0 = w^2 + 7w + 12 simply look at the factors of 12 1 x 12 2 x 6 3 x 4 now consider (w + a)(w + b) = w^2 + aw + bw + ab = w^2 + (a+ b)w + ab since you know 3 x 4 = 12 , and 3 + 4 = 7 this give you 0 = (w + 3) (w + 4) or f(w) = (w + 3)(w + 4) solving for zero w = either -3 or -4 as (-3 + 3)(-3 + 4) = (0)(1) = 0 or (-4 + 3)(-4 + 4) = (-1)(0) = 0 so depending on what you are actually looking for the answer is w^2 + 7w +12 = (w + 3)(w + 4) or -3 and -4
224
whats w stand for? -7w + 3(w+2)= -14
Ill assume you mean for an are of a rectangle. w will stand for width. So you know the equation for a rectangle is L*W, so if length is 7W, then the area is 7W*W=Area or 7W^2
509w
As a term of an expression in math, 72w means 7 times w
7w - 4w - 6w = (7 - 4 - 6)w = -3w
7w=122 122/7= 17.43 w=17.43
Perimeter = length + length + width + width Let "w" = width, then "7w" must equal the length (because it's 7 times the width) 7w + 7w + w + w = perimeter 16w = perimeter
-36 + 2w = -8w + w -36 + 2w = -7w -36 = -7w - 2w -36 = -9w w = -36/-9 = 4
-4
"16-7w plus 14-6w" is an algebraic expression - not an equation nor an inequality. It cannot be solved. So there is no way to determine the value of w and therefore the value of w-1.
I understand this equation to be 7w = 42. The principle we use for solving equations like this one is that we can do the same thing to both sides of the equation and the equation will still be _true_. We want the 'w' by itself. This implies ridding the left side of the 7. We can turn it into a one (1) by dividing it by 7. But if we do that to the left side of the equation then we must also do that to the right side. 7w/7 = 42/7 1w = 6 or w = 6, the result.